PKM Pelatihan Easy Grammar di LKSA Ar Ridho - Anggini, Wulan Yulian; Desnaranti, Laila; Putra, Febby Pratama (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2024)
In learning English, students often find it difficult to learn English grammar. Grammar in English lessons is considered difficult by some of them, making English less popular. Actually, when a teacher can deliver simple grammar instruction, the students will find it much easier to learn and they come to appreciate English. The purpose of this activity is to provide training to caregivers at LKSA Ar Ridho so that foster children there can be helped in understanding Grammar by providing easy Grammar teaching, which is Easy Grammar. The expected output by holding this Easy Grammar training is to increase knowledge about Grammar in English to the caregivers in order that foster children there become happy and enthusiastic in learning English which they initially considered difficult. The community service team along with the foundation's management held a discussion where the results of the discussion agreed that the community service team could organize activities that could help caregivers to be able to teach foster children to learn English easily by studying Easy Grammar. The output target resulting from this community service activity is in the form of knowledge that will be obtained by the caregivers so that they can teach the children in their care.